1985
DOI: 10.1007/bf01332604
|View full text |Cite
|
Sign up to set email alerts
|

A two-level system with induced transitions as a model of stress relaxation

Abstract: This paper outlines the basic features of a two-level cooperative model of the stress relaxation in solids. In contrast to similar models presented earlier, the transitions between the two energy levels can take place in both directions, the relaxation process thus assuming a quasi-equilibrium character. The kinetics of this model are the same as obtained in the model where the transitions take place from the higher to the lower level only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In earlier works [6][7][8] it has been shown that the cooperative model gives the time-dependent stress during the relaxation as s~ e -ts/~ -a(t) = EeS/13 1…”
Section: Determination Of the Dynamic-mechanical Propertiesmentioning
confidence: 99%
See 4 more Smart Citations
“…In earlier works [6][7][8] it has been shown that the cooperative model gives the time-dependent stress during the relaxation as s~ e -ts/~ -a(t) = EeS/13 1…”
Section: Determination Of the Dynamic-mechanical Propertiesmentioning
confidence: 99%
“…T s=l --where 7: is the relaxation time, sm the maximum size (the multiplicity) of the phonon clusters, fl a parameter determining the shape of the relaxation curve and z a constant related to the physical parameters of the system converting the stress rate &r/dt to pure numbers [8]. In eq.…”
Section: Determination Of the Dynamic-mechanical Propertiesmentioning
confidence: 99%
See 3 more Smart Citations